SaaS cloud computing in small and medium enterprises: a comparison between Germany and New Zealand. (2015) - Dillon, Stuart; Vossen, Gottfried
Cloud sourcing and cloud computing have become de-facto standards in recent years for a range of applications. Cloud solutions are attractive for a number of reasons including ease of use, pricing, availability, scalability, and reliability. In particular, small and medium enterprises (SMEs) whose core competencies do not include information technology (IT) can benefit from cloud sourcing, since they can essentially outsource their IT to an external provider. Previous empirical research on cloud sourcing in SMEs, including work by one of the authors, has largely focused on single context (country) cloud adoption issues. This research makes a significant contribution to this emerging field by conducting an international survey of cloud computing adoption and perspectives of SMEs, across two countries: Germany and New Zealand, and seeks to clarify and compare their views of cloud sourcing. Starting with the actual IT situation, we show the prerequisites as well as the reasons in favour of and against a use of the cloud. We then show that the views of SMEs differ in some significant respects between the two countries, and we draw conclusions that can help towards a better design and delivery of cloud software and services that suit SMEs.